Correlation of Single-Photon Emission Computed Tomography Results With Clinical and Intraoperative Findings in Painful Total Ankle Replacement. (June 2020) - Gurbani, Ajay; Demetracopoulos, Constantine; O'Malley, Martin; Deland, Jonathan; Cody, Elizabeth; Sofka, Carolyn; Scharf, Stephen; Ellis, Scott
Background: Evaluating pain after total ankle replacement (TAR) is often difficult, and traditional imaging modalities do not always adequately assess potential etiologies of failure. Our study adds to the current understanding of single-photon emission computed tomography combined with conventional computed tomography (SPECT-CT) as a diagnostic tool for painful TAR. We hypothesized that SPECT-CT would be predictive of clinical and intraoperative findings and would be more useful than magnetic resonance imaging (MRI) in our cohort. Methods: A retrospective review of SPECT-CT imaging performed at our institution in patients with painful TAR from January 2014 to November 2018 was conducted. A total of 37 patients were identified, and 28 of them underwent revision surgery. Additionally, 19 patients had an MRI during the same time frame. Imaging results were compared to the documented clinical findings and intraoperative findings during revision surgery. Results: Of the 37 patients included, 89.2% (33/37) had SPECT-CT results that were consistent with the ultimate diagnosis documented in the medical record. Aseptic loosening (12/33) and impingement (11/33) were the most common diagnoses. Among patients who underwent revision surgery, SPECT-CT results were consistent with intraoperative findings in 26 of the 28 (92.9%) cases. In the 19 patients who also underwent MRI, the findings were consistent with clinical findings 36.8% (7/19) of the time. Conclusion: In our cohort, there was high consistency between SPECT-CT results and documented clinical diagnoses. SPECT-CT also demonstrated high consistency with intraoperative findings during revision surgery. Compared with MRI, SPECT-CT proved more useful in establishing a diagnosis of pain after TAR. Level of Evidence: Level III, comparative series.